GANGGUAN OTONOM PADA PEKERJA TERPAJAN TIMBAL KRONIK BERDASARKAN PEMERIKSAAN SYMPATHETIC SKIN RESPONSE DAN FAKTOR FAKTOR YANG MEMPENGARUHI - Ekawati Dani Yulianti*, Fitri Octaviana*, Manfaluthy Hakim*, Joedo Prihartono** (NEURONA, 2010)
INTRODUCTION LEAD HAS TOXIC PROPERTY TO THE NERVOUS SYSTEM INORGANIC LEAD COULD DAMAGE PERIPHERAL NERVE SYSTEM CAUSING NEUROPATHY AUTONOMIC NEUROPATHY IN LEAD EXPOSED WORKERS IS OFTEN SUB CLINICAL HOWEVER SYMPATHETIC SKIN RESPONSE SSR ABNORMALITY WAS FOUND IN ASYMPTOMATIC CHRONICALLY EXPOSED TO LEAD WORKERS